2015
DOI: 10.1038/ismej.2015.78
|View full text |Cite
|
Sign up to set email alerts
|

Long-term soil transplant simulating climate change with latitude significantly alters microbial temporal turnover

Abstract: To understand soil microbial community stability and temporal turnover in response to climate change, a long-term soil transplant experiment was conducted in three agricultural experiment stations over large transects from a warm temperate zone (Fengqiu station in central China) to a subtropical zone (Yingtan station in southern China) and a cold temperate zone (Hailun station in northern China). Annual soil samples were collected from these three stations from 2005 to 2011, and microbial communities were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(73 citation statements)
references
References 68 publications
3
68
1
1
Order By: Relevance
“…Microbial community structural analysis catalogs active, inactive, and dead microbial DNA in soil (Carini et al, ) and thus contains both current and historical community data in its signal. Nonetheless, observations of variation in community structure across regions and incubation day, and sensitivity and insensitivity of Acidobacteria and Proteobacteria to temperature, respectively, suggest that our analyses captured sufficient information to reflect active microbial populations (Castro et al, ; Liang et al, ). The decoupling of structure and function is not uncommon (Allison & Martiny, ; Graham et al, ), and in our case may indicate that our structural analysis is sensitive to changes in portions of the community for which we do not measure the function, such as anaerobes.…”
Section: Discussionmentioning
confidence: 92%
“…Microbial community structural analysis catalogs active, inactive, and dead microbial DNA in soil (Carini et al, ) and thus contains both current and historical community data in its signal. Nonetheless, observations of variation in community structure across regions and incubation day, and sensitivity and insensitivity of Acidobacteria and Proteobacteria to temperature, respectively, suggest that our analyses captured sufficient information to reflect active microbial populations (Castro et al, ; Liang et al, ). The decoupling of structure and function is not uncommon (Allison & Martiny, ; Graham et al, ), and in our case may indicate that our structural analysis is sensitive to changes in portions of the community for which we do not measure the function, such as anaerobes.…”
Section: Discussionmentioning
confidence: 92%
“…However, PLFAs had limited resolution for fingerprinting in quantifying microbial community. At our study site, simulated climate warming by southward soil transplantation led to a faster succession rate of bacterial communities as well as lower species richness and compositional changes than in situ and northward soil transplantation (Liang et al, ). However, it remains unclear how fungal communities respond to simulated climate changes at this site.…”
Section: Introductionmentioning
confidence: 83%
“…Therefore, reciprocal soil transplantation experiments provide a valuable strategy to address the question of how soil microbial communities respond to climate differences under comparable soil physicochemical conditions (Waldrop & Firestone, 2006;Zumsteg, Bååth, Stierli, Zeyer, & Frey, 2013). Recently, this strategy has provided important insights into elucidating the effect of climate changes on microbial communities (Balser & Firestone, 2005;Liang et al, 2015). PLFA analysis showed that a fungal biomarker was significantly changed by soil transplantation while bacterial biomarkers remained largely unchanged (Balser & Firestone, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…By linking the diversity, composition and structure of microbial communities with their ecological functions, research was conducted using metagenomic sequencing (Yooseph et al, 2010), COG and SEED annotations (Burke et al, 2011a), GeoChip (Lu et al, 2012) and network analysis (Fuhrman, 2009). Those studies showed that microbial community assembly was largely based on functions rather than phylogenetic similarity and could adapt to new environments by changing community structure and composition (Langenheder and Szekely, 2011;Liang et al, 2015;Logue and Lindstrom, 2010). In this study, our results showed that the most dominant phylum is Proteobacteria, including δ-Proteobacteria and γ-Proteobacteria, which exhibited higher abundance at CZ and generally function in sulfate-reduction, sulfuroxidization and nitrate assimilation (Allen et al, 2001;Asami et al, 2005;Castine et al, 2009;Kawahara et al, 2008).…”
Section: Certain Microbial Groups Enriched In Response To Seaweed Culmentioning
confidence: 99%